SIMPLE TECNOLOGY IN RURAL COMMUNITIES IN CHIWETEL EJIFOR THE BOY WHO HARNESSDED THE WIND (2019) - Elisa Fatika Risda; M. Thoyibi (JURNAL KONFIKS, 2025)
This study aims to analyze the representation of simple technology in rural communities as depicted in Chiwetel Ejiofor’s The Boy Who Harnessed the Wind (2019). Simple technology is defined as a locally sourced, low-cost, and practical form of innovation that can be constructed and maintained using basic materials and community knowledge. Employing a descriptive qualitative method and the Sociology of Literature framework by Swingewood and Laurenson, this research examines how functionality, feasibility, and flexibility of simple technology are portrayed through William Kamkwamba’s efforts to build a windmill from recycled objects. Data were collected through analysis of film dialogue, visual imagery, audio elements, and supporting literature. The findings show that simple technology in the film functions not only as a mechanical tool but also as a symbol of creativity, resilience, and social solidarity. William’s windmill provides a direct solution to water scarcity while restoring collective hope and cooperation in a community facing environmental crisis and structural poverty. The film also emphasizes the importance of education, persistence, and local knowledge in enabling community-driven innovation. This study concludes that simple technology plays a vital role in empowering marginalized rural communities because it is contextual, sustainable, and rooted in everyday problem-solving. Furthermore, the film demonstrates how cinematic representation of technology can serve as social reflection and inspire grassroots innovation in developing countries.